Analisis Toolpath Variasi Zig Zag Dan Spiral Mesin CNC Router Terhadap Benda Kerja Berbahan Acrylic - Juniantoro, Gilang Bagus, Bambang Waluyo F, ST. MT, Nurmuntaha A.N, ST,Pg,DIP (2016)
The purpose of this research is to determine the feeding speed of two different toolpath due to the feeding speed variation in the making process of the acrylic based workpiece. This research discuss about the construction process of CNC machine with the early stage of preparing the tools and materials, and also designing and constructing the desired machine by using the aluminium and iron material. The next stage is preparing the acrylic based workpiece as the testing material. The machining process was conducted by applying the zig zag and spiral toolpath and the result of both toolpaths will be discussed. From the test result of zig zag toolpath, it was found that the highest cutting speed occurs at the feeding speed of 300mm/min, that was 34.852m/mm. While from the spiral toolpath, it showed that the highest cutting speed occurs at the feeding speed of 300mm/min, that was 35.958m/mm. It can be concluded that the higher the feeding speed, the higher the cutting speed as well. From these two toolpath, it is determined that the zig zag toolpath has the higher cutting speed than that of the spiral toolpath. Key words: Toolpath, CNC Router, Acrylic